Standardised treatment and monitoring protocol to assess safety and tolerability of bacteriophage therapy for adult and paediatric patients (STAMP study): protocol for an open-label, single-arm trial. Issue 12 (9th December 2022) - Khatami, Ameneh; Foley, David A; Warner, Morgyn S; Barnes, Elizabeth H; Peleg, Anton Y; Li, Jian; Stick, Stephen; Burke, Nettie; Lin, Ruby C Y; Warning, Julia; Snelling, Thomas L; Tong, Steven Y C; et al.
Abstract : Introduction: There has been renewed interest in the therapeutic use of bacteriophages (phages); however, standardised therapeutic protocols are lacking, and there is a paucity of rigorous clinical trial data assessing efficacy. Methods and analysis: We propose an open-label, single-arm trial investigating a standardised treatment and monitoring protocol for phage therapy. Patients included will have exhausted other therapeutic options for control of their infection and phage therapy will be administered under Australia's Therapeutic Goods Administration Special Access Scheme. A phage product with high in vitro activity against the targeted pathogen(s) must be available in line with relevant regulatory requirements. We aim to recruit 50–100 patients over 5 years, from any public or private hospitals in Australia. The standardised protocol will specify clinical assessments and biological sampling at scheduled time points. The primary outcome is safety at day 29, assessed by the frequency of adverse events, and overseen by an independent Data Safety Monitoring Board. Secondary outcomes include long-term safety (frequency of adverse events until at least 6 months following phage therapy), and feasibility, measured as the proportion of participants with>80% of minimum data available for analysis. Additional endpoints assessed include clinical response, patient/guardian reported quality of life measures, phage pharmacokinetics, human host immune responses and microbiome analysis. All trial outcomes will be summarised and presented using standard descriptive statistics. Ethics and dissemination: Participant inclusion will be dependent on obtaining written informed consent from the patient or guardian. The trial protocol was approved by the Sydney Children's Hospitals Network Human Research Ethics Committee in December 2021 (Reference 2021/ETH11861). In addition to publication in a peer-reviewed scientific journal, a lay summary of study outcomes will be made available for participants and the public on the Phage Australia website (https://www.phageaustralia.org/ ). Trial registration number: Registered on ANZCTR, 10 November 2021 (ACTRN12621001526864; WHO Universal Trial Number: U1111-1269-6000).